DESIGN OF ACCOUNTING INFORMATION SYSTEM THROUGH ERP SYSTEM DEVELOPMENT TO IMPROVE INTERNAL CONTROL (STUDY ON SME CHIPSANG INDONESIA) - Frisdianalis Tihta Ficahyani; Abidin, Fityan Izza Noor (International Journal Multidisciplinary (IJMI), 2025)
Objective: The purpose of this study is to describe the business process before and after the design of the accounting information system through the development of an enterprise resource planning system. Method: This study uses a purposive sampling technique for determining informants taken from respondents of IKM Chipsang Indonesia. This study uses a qualitative approach with a data validity test, namely data triangulation. Results: The results of this study indicate that the design of the accounting information system processes accounting data originating from various business process activities of the company into accounting information needed to reduce risk when making decisions. The success factor of the design can be seen from human resources who are willing to accept information technology and understand the ERP system in order to achieve good internal control. Novelty: This study highlights the integration of ERP system design with qualitative insights from a specific SME case (IKM Chipsang Indonesia), offering a contextual understanding of how human resource readiness influences internal control through information system adoption.